Preparation and characterization of poly(lactic acid)-based contact-active antimicrobial surfaces - Aynali, Figen; Doganci, Erdinc; Balci, Huseyin; Cetin, Metin; Ozkoc, Guralp; Sadikoglu, Hasan (SPRINGER, 2023)
Poly(lactic acid) (PLA)-based contact-active antimicrobial surfaces were successfully fabricated via the spray coating method. For this purpose, firstly two separate antimicrobial polymers were synthesized by introducing alkyne functionalized quaternary ammonium salt into clickable copolymer containing 30 mol% and 5 mol% of quaternary ammonium salt on their backbones. Then, these synthesized polymers were applied to coat one surface of the neat PLA films (PLA/PEG, 90/10) at the rate of 5, 15, and 25 times, respectively. Afterward, the biocidal effect of these films was considered against Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus) bacteria by the way of contact-active method. It was observed that the films coated with polymer containing 30 mol% of quaternary ammonium salt (QAS), even at the lowest coating amount, showed a considerably active antimicrobial property against both bacteria. The thermal, mechanical, and barrier properties of coated films were also investigated. In addition, a cytotoxicity test was performed, and it was found that the PLA film was nontoxic when it was coated with polymer containing 5 mol% of quaternary ammonium salt, even at a high coating amount. For a polymer containing 30 mol% of quaternary ammonium salt on its backbone, it was necessary to coat the films at a low rate for acceptable cytotoxicity. In conclusion, due to the contact-active behavior of covalently attached antimicrobial agents, high antibacterial activity, suitable mechanical properties, and acceptable cytocompatibility, these antimicrobial surfaces can be considered as a potential candidate for bio-based materials.
Keywords: Poly(lactic acid); Antimicrobial surface; Spray coating; Contact-active; RING-OPENING POLYMERIZATION; QUATERNARY AMMONIUM-SALTS; CLICK CHEMISTRY; POLYLACTIC ACID; POLYMERS; FOOD; COMBINATION; STRENGTH; BLENDS; FILMS; Chemistry; Materials Science